The Ig heavy chain protein but not its message controls early B cell development - Aslam, Muhammad Assad; Alemdehy, Mir Farshid; Hao, Bingtao; Krijger, Peter H L; Pritchard, Colin E J; de Rink, Iris; Muhaimin, Fitriari Izzatunnisa; Nurzijah, Ika; van Baalen, Martijn; Kerkhoven, Ron M; van den Berk, Paul C M; Skok, Jane A; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Development of progenitor B cells (ProB cells) into precursor B cells (PreB cells) is dictated by immunoglobulin heavy chain checkpoint (IgHCC), where the IgHC encoded by a productively rearranged allele assembles into a PreB cell receptor complex (PreBCR) to generate signals to initiate this transition and suppressing antigen receptor gene recombination, ensuring that only one productive allele is expressed, a phenomenon known as allelic exclusion. In contrast to a productively rearranged allele, the messenger RNA (mRNA) ( ) from a nonproductively rearranged allele is degraded by nonsense-mediated decay (NMD). This fact prohibited firm conclusions regarding the contribution of stable to the molecular and developmental changes associated with the IgHCC. This point was addressed by generating the mouse model from mice having a premature termination codon at position +5 in leader exon of allele. This prohibited NMD, and the lack of a transmembrane region (∆TM) prevented the formation of any signaling-competent PreBCR complexes that may arise as a result of read-through translation across premature Ter5 stop codon. A highly sensitive sandwich Western blot revealed read-through translation of message, indicating that previous conclusions regarding a role of in establishing allelic exclusion requires further exploration. As determined by RNA sequencing (RNA-Seq), this low amount of IgHC sufficed to initiate PreB cell markers normally associated with PreBCR signaling. In contrast, the knock-in allele, which generated stable but no detectable IgHC, failed to induce PreB development. Our data indicate that the IgHCC is controlled at the level of IgHC and not expression.